(untitled) (Fiep Bulletin - online, 2012)
The frequency of using one side of the body is related to lateral preference concept. The Global Lateral Preference Inventory (GLPI) is used to diagnosis the lateral preference (Okazaki et al., 2010). In this inventory there are questions related to daily tasks which encompassed superior limbs (SL) and inferior limbs (IL), trunk, hearing and vision. Despite of GLPI contributions for understanding lateral preference, there is a lack of studies that analyze the coherence between answers acquired by the questionnaire and the practice performance of these tasks. Therefore this study realized the theoretical-practical validation of GLPI-B (experiment 1) and GLPI-C (experiment 2). In experiment 1, 14 undergraduate students (mean age=21,43 years, DP=2,77) were tested and in experiment 2, 18 undergraduate students (mean age=23,16 years, DP=4,56). The participants performed the proposed tasks at GLPI-B and GLPI-C in theory and practice. Both theoretical and practical GLPI were performed with 4 trials at each task by the participants and the results were classified as high left-handed, moderated left-handed, indifferent, moderated right-handed and high right-handed. After the performance of both GLPI (theoretical and practical) a correlation analysis were made which showed r=0,946 (P<0,001) for GLPI-B and r=0,77 (P<0,001) for GLPI-C. The participants were classified as moderated right-handed in both conditions of GLPI for SL and IL. Accordingly the GLPI inventory showed to be a valid tool to analyze lateral preference.